Elizabeth i eaudiobook Red rose of the house of tudor, england, 1544. - Lasky, Kathryn (Royal Diaries, 2005)
Welcome to the bizarre court of Henry VIII, where even a princess fears losing her head like her mother. Elizabeth hides her tenacious personality from everyone, especially her father. Your 21st-century kid will enjoy Elizabeth's "treasonous thoughts" and glimpse the daily life of a young woman who ascended the throne at 25 and went on to rule her country for 45 years.